Place of spiritual rehabilitation in the system of social rehabilitation of children with deviant behavior - Baranov, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article is devoted the problem of spiritual rehabilitation of children with a deviant conduct, educated in child’s establishments of social rehabilitation. In this article examined deviation in individual-personality development of children and conditionality their psychological deviation. A spiritual rehabilitation is examined as a component of the system of social rehabilitation, and a psychological rehabilitation is examined, foremost, as a rehabilitation spiritual. Terms, cooperate education of spirituality of personality of teenager, are examined - pupil of social-rehabilitation establishment.